PERAN KEPALA SEKOLAH DAN PENGAWAS DALAM SUPERVISI AKADEMIK DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH DASAR - Rahayu Rahmadani; Ira Maya Sofa; Nova Arianti; Ratna Juita; Ramayulis Rahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The quality of education in elementary schools is greatly influenced by the quality of the learning process, one of which is through academic supervision carried out by school principals and school supervisors. This study aims to examine the roles of both parties in the implementation of academic supervision and their contributions to improving the quality of basic education. The research method used is a literature review with a literature analysis approach from primary and secondary sources, including educational management theory, government policies, and previous research results. The analysis results indicate that school principals play a direct role in teacher development through classroom visits and feedback, while school supervisors have a broader role in evaluating and developing the professionalism of both school principals and teachers. Synergy between the two is a key factor in the effectiveness of supervision.